Extended cognitive behavior therapy for cigarette smoking cessation - Killen, Joel D. (2008)
PRIMARY AIM: Examine the effectiveness of extended cognitive behavior therapy (CBT) in promoting longer-term smoking abstinence. DESIGN: Open-label treatment phase followed by extended treatment phase. Randomization conducted prior to entry into open-label treatment phase; analysis based on intention-to-treat to avoid threat of selection bias. SETTING: Community smoking cessation clinic. PARTICIPANTS: A total of 304 adult smokers (≥18 years of age; ≥10 cigarettes/day). INTERVENTION: Open-label (8 weeks): all participants received bupropion SR, nicotine patch, CBT. Extended treatment (12 weeks): participants received either CBT + voicemail monitoring and telephone counseling or telephone-based general support. MEASUREMENTS: Seven-day point prevalence abstinence, expired-air carbon monoxide. RESULTS: At week 20 follow-up, CBT produced a higher 7-day point prevalence abstinence rate: 45% versus 29%, P = 0.006; at 52 weeks the difference in abstinence rates (31% versus 27%) was not significant. History of depression was a moderator of treatment. Those with a positive history had a better treatment response at 20 weeks when assigned to the less intensive telephone support therapy (P < 0.05). CONCLUSION: The superiority of CBT to 20 weeks suggests that continued emphasis on the development of cognitive and behavioral strategies for maintaining non-smoking during an extended treatment phase may help smokers to maintain abstinence in the longer term. At present, the minimum duration of therapy is unknown.